Main directions of development of innovative business financing in Ukraine - Samorodov , Borys; Kotkovskyi , Volodymyr (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
The article examines the loan market for Ukrainian businesses, highlighting key factors such as demand, supply, external environment, loan portfolio characteristics, and results from previous periods. These factors collectively shape the state of the business loan market, influencing the development of innovative entrepreneurship in Ukraine. The challenges posed by Basel III requirements, such as increased costs for long-term loans, are discussed, revealing the limited availability of project financing. Despite high demand for innovative business financing, the absence of a centralized government agency to coordinate efforts remains a significant barrier. A comprehensive loan market index is proposed to assess the state of financing for innovative businesses, incorporating supply-demand dynamics, external factors, and historical performance. This index enables qualitative evaluation and informs policy development to support entrepreneurship. Several targeted financing programs are outlined, including support for skills and knowledge development, commercialization, prototype creation, and lean manufacturing implementation. Additionally, innovative funding mechanisms such as co-financing and partnerships with microfinance organizations and commercial banks are explored. The study emphasizes the need for centralized coordination and streamlined support systems to address challenges like organizational duplication and unclear program goals. Recommendations include developing a coherent strategy, minimizing regulatory burdens, and leveraging preferential loans for innovative entrepreneurship. These measures aim to enhance access to financial resources, foster innovation, and drive sustainable economic growth in Ukraine.